Hypericum perforatum L. supplementation protects sciatic nerve injury‐induced apoptotic, inflammatory and oxidative damage to muscle, blood and brain in rats. (16th May 2017) - Uslusoy, Fuat; Nazıroğlu, Mustafa; Övey, İshak Suat; Sönmez, Tolga Taha
Abstract: Objectives: This study was conducted to explore whether Hypericum perforatum L . (HPL) as a potent antioxidant protects against oxidative stress, cytokine production and caspase expression in muscle (soleus), brain and blood of sciatic nerve injury (SNI)‐induced rats. Methods: Thirty‐five rats were equally divided into five groups. The first and second were used as untreated control and sham control groups, respectively. The third, fourth and fifth were sham + HPL, SNI and SNI + HPL groups, respectively. The third and fifth groups received 30 mg/kg HPL via gastric gavage for 28 days. Key findings: High levels of muscle, brain and red blood cell (RBC) lipid peroxidation, plasma cytokine (TNF‐α, IL‐1β and IL‐2), muscle PARP, caspase 3 and 9 expression levels were decreased by HPL treatments. Plasma glutathione peroxidase (GPx) activity, α‐tocopherol and melatonin, muscle, brain and RBC reduced glutathione (GSH) concentrations were decreased by SNI induction, whereas their values were increased by HPL treatments. β‐carotene and retinol concentrations did not change in the five groups. Conclusion: HPL may play a role in preventing SNI‐induced inflammatory, oxidative and apoptotic blood, muscle and brain damages through upregulation of the GSH and GPx values but downregulation of PARP, caspase level and cytokine production in SNI‐induced rats.